A Narrativa na ponta dos dedos: Texto e imagem nas obras de Sávia e Ângela Dumont - Barbosa, Maria Flávia Pereira (2017)
This research is dedicated to analyze two works: Alberto, sonhos e alinhavos – a ousadia de ir além do chão, by writer Sávia Dumont and Águas emendadas, written by Ângela Dumont. With illustrations prepared by the group Matizes Dumont, the works differ in their double literary composition: by the verbal text, which dialogues with other texts proper to the popular tradition as songs and trovas; And by embroidery, in the illustration position. Both elements, together, make up unique narratives intertwined for the construction of a sensitive plot, in which childhood, memory, tradition and part of Brazilian cultural identity stand out. In the trajectory to examine the works in detail, theoretical references were consulted that could differentiate the poetic images, born of the literary construct that evokes metaphors and symbols for the formulation of meaning with the readers, as well as the pictorial images. Even so, it was necessary another look at the embroidered illustrations, given the cultural, historical and often affective tradition inherent in them, so that, finally, one could deduce their contribution to the construction of the plot in each work . This choice made it consulted illustration scholars of literary texts as Luiz Camargo (1995), Ricardo Azevedo (1997), Guto Lins (2002) and André Mendes (2007) . The concepts of Paul Zumthor, Jerusa Pires Ferreira (2010), Câmara Cascudo (1984) were essential for the observation of the marks of culture and identity present in the narratives. Already the poetics and the images of the works were analyzed from the thought of Gaston Bachelard. In his reflections on the reverie and essence of literary images and his poetics of elements and spaces, Bachelard provided instruments for the detailed appreciation of works in their totality. Other theorists also contributed to the analysis of these works, considered as innovative in their aesthetic literary construction. It is concluded through these analyzes that the textual and visual composition of literary works can result in new and quite significant objects from the aesthetic and cultural point of view.